(untitled) (International Journal of Mathematics and Physics, 2015)
In this graduation diploma project I present a new mobile application for IOS Operating System in Xcode IDE (Integrated Development Environment). It is employed in order to overcome the problem of traffic flow in cities like Almaty and Astana. Moreover, I designed a software which enables us to easily find nearest drivers for passengers, and vice versa, by using bjective C programming language. Objective C can be very efficient there, since it is a general-purpose, object-oriented programming language and uses model-view-controller design pattern.My mobile application makes it possible for users, i.e. both drivers and passengers, to select trustworthy drivers via simplerequests.